The The Influence of Green Marketing Mix and Environmental Awareness on Oat Milk Purchase Decision in the Special Region of Yogyakarta Province - Aurelia, Vena Bianda; Masyhuri; Suryantini, Any (HABITAT, 2024)
Environmental issues have led to changes in people's lifestyles, making them more environmentally conscious, especially when purchasing products, including selecting the foods they consume. One commonly consumed food product is milk. Cow's milk production in Indonesia has not yet met domestic demand, necessitating alternative milk options such as plant-based milk like oat milk. The latest marketing concept, green marketing, modifies the 4P marketing mix into a green marketing mix, which influences purchasing decisions. Environmental awareness and consumer attitudes can also impact purchasing decisions. The aim of this study is to determine the influence of the green marketing mix and environmental awareness on purchasing decisions, both directly and mediated by consumers' attitudes. This research is a descriptive quantitative study. The analysis technique used is SEM-PLS, with 215 respondents. The sample was determined using purposive sampling and the sample size was determined using the rule of thumb from SEM. The results of this study indicate that the green marketing mix, environmental awareness, and consumers' attitudes directly influence purchasing decisions. Consumers' attitudes only mediate the effects of green price, green promotion, and environmental awareness on purchasing decisions.